How to imagine a non-capitalist measure?: Going beyond the value production with Spinoza's concept of expression. Issue 3 (2nd October 2021) - Krzeski, Jakub
Abstract : This article argues that the task to develop a non-capitalist measure suitable for coordinating the process of satisfying expanding collective needs in the postcapitalist society might benefit from engaging with Spinoza's philosophy and, in particular, his notion of expression. This task is presented as crucial, once the Marxian law of value is grasped in its double function. Although the law of value univocally lies at the heart of Marx's attempt to understand the economic law of motion of capitalist society, when approached from the perspective of working towards a postcapitalist society it appears as something to be transcended. This is because the law of value not only explains the class nature of capitalist society but at the same is a means through which class relations are reproduced in the first place. In turn, rendering this mechanism inoperable entails discarding a capitalist measure as a means of the imposition of work on living labour. In the fragment on the machines in the Grundrisse Marx himself theorized a crisis of capitalist measure, i.e. circumstances under which social wealth is no longer represented through value. Once the socially necessary labour time seizes to govern production in a given society, a window of opportunity presents itself for developing a non-capitalist measure. One, which according to Marx, relies on the disposable time of the working class instead of labour time. As it is argued throughout this paper, this is where Spinoza and his concept of expression come to the fore. By introducing Spinoza to the problem of non-capitalist measure via the philosophical project of Antonio Negri, we acquire conceptual tools to further develop logic according to which such measure must operate, if it is to create favourable conditions for the development of social wealth, instead of restricting it by means of representing it through value.